2014
DOI: 10.1139/cjc-2013-0563
|View full text |Cite
|
Sign up to set email alerts
|

Diatomic molecule energies of the modified Rosen−Morse potential energy model

Abstract: We solve the Schrödinger equation with the modified Rosen−Morse empirical potential model to obtain rotation-vibrational energy spectra and unnormalized radial wave functions. The vibrational energy levels calculated with the modified Rosen−Morse potential model for the 61Πu state of the 7Li2 molecule and the X3Π state of the SiC radical are in better agreement with the Rydberg−Klein−Rees data than the predictions of the Morse potential model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…This finding implies that the use of the Rosen-Morse and the Modified-Rosen-Morse potential function within the framework of the semi-classical approximation has significantly improved the accuracy of the calculation of vibrational energies from the Morse potential, especially for higher vibrational states. This finding was also reported by Tang et al [44]. They fitted the potentials to the well-known Rydberg-Klein-Rees (RKR) data points of the Li2 molecule.…”
Section: Improved Vibrational Energies From the (Modified) Rosen Morse Potentialsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding implies that the use of the Rosen-Morse and the Modified-Rosen-Morse potential function within the framework of the semi-classical approximation has significantly improved the accuracy of the calculation of vibrational energies from the Morse potential, especially for higher vibrational states. This finding was also reported by Tang et al [44]. They fitted the potentials to the well-known Rydberg-Klein-Rees (RKR) data points of the Li2 molecule.…”
Section: Improved Vibrational Energies From the (Modified) Rosen Morse Potentialsupporting
confidence: 85%
“…This finding suggested that the modified Rosen Morse potential was more potent than the Morse potential in describing the interaction of diatomics. This conclusion was supported by the study of Tang et al [44], who solved the Schrödinger equation of some diatomics with some potential functions and found that the Modified Rosen Morse potential was better in fitting with experimental data. It is interesting to note that for the H2 molecule (the lightest molecule considered here), the Morse potential was somehow better than both Rosen Morse and the Modified Rosen Morse potential, with errors about 0.31%, 0.37%, and 0.39%, respectively.…”
Section: Comparison With Experimental Values and Literaturementioning
confidence: 64%
“…In 2014, Tang et al [198] presented a study about the vibrational energy levels calculated using the MRM potential for 7 Li 2 (6 1 Π u ) and SiC ( X 3 Π), and both were in good agreement with the experimental RKR data. For these diatomic systems, Tang et al also compared the MRM potential with the MOR [7], FM [113], VAR [14] III, and Lippicott [199] potentials.…”
Section: Potential Energy Functionsmentioning
confidence: 73%
“…Because of their various applications, solutions of the relativistic and nonrelativistic wave equations have been utilized in various quantum potential interactions utilizing different techniques [13,14]. These methods incorporate 1/ N shifted expansion procedure [15], Nikiforov-Uvarov approach [16,17], asymptotic iteration method [18], factorization method [19,20], formula technique [21], supersymmetric approach [22,23], ansatz methodology [24], Laplace transform approach [25,26], functional analysis approach [27,28], proper quantization rule [29], and others [30,31].…”
Section: Introductionmentioning
confidence: 99%